O papel do Estado do Paraná no regime de colaboração para a formação inicial e continuada dos professores dos municípios - Bach, Maria Regina (2012)
This study seeks to identify the existence of a public policy in the State of Parana, which contemplates the Collaboration Regime among federal agencies to promote the initial and continuing training of teachers as prescribed in the legislation of education, especially considering the collaboration of the State to its 399 municipal districts. It's supported on the problem of Collaboration Regime poor visibility and its indefinite way while public policy, that's to say, the legal prescription as insufficient to be accomplished while stimulating the education offer and quality in the municipal districts and, therefore, in the State of Paraná. Through bibliographic research we observed that the Collaboration Regime started in the context of educational reforms implemented between the XX and XXI centuries, which came from the end of XX century Brazilian State reform. Then, in the first decade of century XXI, it happens more strongly on the initial and continuing training of teachers, making it still with the same principles limitations, commanded by international capital and its interests in maintaining the capitalist order. For this analysis, the study has the historical-materialist dialectics as theoretical framework, which means that society is built - not given - and is moving, always with possibilities of civil society's activities within the State. By means of public data survey of the State Secretariats of Education and Science, Technology and Higher Education, and using the method of public policy analysis entitled "Process", it was possible to define the actions of the State of Paraná in the period of Requião government , referring to initial and continuing training of local school systems for Early Education and early years of elementary school. Considering the conclusion of diversified actions existence in this way without, however, being constituted as public policy, a proposal is presented, within the limits of an academic study, for its establishment in order to create spaces for discussion with civil society, translate the reality of teacher education in Parana and find out elements and actions capable of contributing with the Municipal districts indeed.